The Lockeport Lockout: An Untold Story in Nova Scotia's Labour History - Reilly, Nolan (Labour / Le Travail, 1985)
This article reviews the book "The Lockeport Lockout: An Untold Story in Nova Scotia's Labour History," by Michael Lynk and Sue Calhoun.
Keywords: CALHOUN, Sue; History; LOCKEPORT Lockout: An Untold Story in Nova Scotia's Labour History, The (Book); LYNK, Michael; Labor; Nonfiction; REVIEWS; books